Analysis of Low Estrogen Receptor (ER+) Breast Carcinomas in a Large Community Breast Cancer Center in Northern California. (28th October 2021) - Bulusu, G; Duncan, K; Wheeler, A
Abstract: Introduction/Objective: Estrogen Receptor (ER) expression in breast cancers is a crucial factor for endocrine therapy in patients with tumors expressing ER in ≥1% of tumor cells. The 2019 guidelines published by ASCO/CAP states that breast cancers that have a 1% to 10% of cells staining Estrogen Receptor (ER) positive should be reported as ER Low Positive cases. This study aims to address this subset of low-positive ER tumors and compare the clinical features to other known breast cancer subtypes. Methods/Case Report: We conducted a retrospective review of a prospectively maintained breast cancer registry from 2013 to 2021 at Mills-Peninsula Medical Center, a Sutter Health Affiliate. The study reviewed patient charts with respect to the pathology report, operative report, chemotherapy regimen, and clinical outcomes. Statistical analyses were conducted using R Project for Statistical Coding, with The Student's T-test used to compare continuous variables. Two-sided P values less than 0.05 indicate statistical significance. Results (if a Case Study enter NA): Our study identified 1316 cases of invasive breast carcinomas, of which 29 (2.16%) demonstrated ER Low-Positive expression. We aimed to evaluate the clinical and pathological features, such as histological grade, ER, PR, HER-2, Ki-67%, and patient age for these tumors. We found that ER Low-Positive tumors demonstrated higher mean histological grade morphology (2.5 out of 3, p<0.001) that was similar to that of Triple Negative Breast Cancers (TNBC) (3 of 3, p<0.001) than to High ER-Positive (1.6 of 3, p<0.001) cancers. Further observations, through examining proliferation rates by utilizing the Ki-67 index, indicate comparative trends between the ER Low-Positive cohort and the TNBC cohort. Conclusion: The results suggest that the ER Low-Positive carcinomas, despite reported as ER-positive cases, present with similar clinicopathological features to those of ER-negative tumors. Through this study and future research, we would like to emphasize a stricter set of guidelines that can be adopted to reduce variability for reporting biomarkers. This standardization will allow oncologists to provide more appropriate treatment options and improve the quality of patient care.